Citizens at Last : The Woman Suffrage Movement in Texas - Temple, Ellen C. (Book collections on Project MUSE., 2015)
"There is so much to be learned from the documents collected here. ... Where better than in this record to find the inspiration to achieve another high point of women's political history?"--The foreword by Anne Firor Scott Citizens at Last is an essential resource for anyone interested in the history of the suffrage movement in Texas. Richly illustrated and featuring over thirty primary documents, it reveals what it took to win the vote.